Perhitungan Persediaan Menggunakan Metode FIFO dan Average pada CV. Mitra Tani Farm - Putri, Alifia Rizkia; Fahmie, Arief; Sari, Febriani Indah; Pradipto, Didit (Jurnal Abdimas Dedikasi Kesatuan, 2025)
ABSTRACTInventory is a company asset that includes tangible goods of the company that are intended to be resold to other parties in a period of normal business activities of the company, which are directly sold or will be processed first by the company and then sold. Internal control over inventory is absolutely necessary considering that this asset is classified as quite liquid. Internal control over inventory should begin when the goods are received (purchased from suppliers).The purpose of this calculation is to find out the inventory calculation at CV. Mitra Tani Farm. By doing this calculation, it simplifies or smoothens the company's operations, both production and sales, so that what is planned and targeted can be achieved without obstacles caused by a lack of goods. The calculation of inventory reports is expected so that all company activities produce good reports, thus making it easier to determine the cost of goods inventory.The calculation results show that the inventory recording carried out by CV. Mitra Tani Farm uses the FIFO method. This method is suitable for use by CV. Mitra Tani Farm in recording its inventory, because this avoids the accumulation of old goods, damaged goods or defects in goods. The author also helps companies to record using the Average method, but each inventory recording at CV. Mitra Tani Farm has the same purchase price and selling price as its initial inventory, so the Average method recording produces the same results as the FIFO method recording. Keywords: Inventory, FIFO method and Average